Critical concepts in the writings of Mikhail Bakhtin - abboud, ourida (El Omda in Linguistics and Discourse Analysis, 2025)
various discourses and texts, and despite the many discussions that critics have had about the value of these concepts, his ideas have spread and transcended local borders, establishing critical theory. - Bakhtin's concepts were based on multiple references between epistemological, philosophical and ideological